ANALISIS PERBANDINGAN KONTRIBUSI PP 46 TAHUN 2013 DENGAN PP 23 TAHUN 2018 TERHADAP REALISASI PAJAK (Studi kasus pada KPP Pratama Bandung Tegallega) - Abiyyu Asdi Pambudi (Epistemik: Indonesian Journal of Social and Political Science, 2021)
This study aims to determine how significant the contribution of PP 46 of 2013 with PP 23 of 2018 towards the Tax Realization at Pratama Bandung Tax Office. The method in this research is descriptive analysis with a quantitativeapproach. The data of this study were obtained from data reports related to the receipt of PP 46 of 2013 and PP 23 of 2018 as well as the total tax revenue from the sampling technique using a purposive sampling technique. In analyzing data, this study uses statistical analysis of contribution analysis and hypothesis testing using the t-test. Based on the calculation of contribution analysis and t-test with the help of SPSS 25 software, it is found that (1) The contribution of PP 46 of 2013 to the Realization of Taxes falls into the category of very less with an average percentage of 3.2% at KPP Pratama Bandung Tegallega, (2 ) The contribution of PP 23 of 2018 to the Realization of Taxes falls into the category of very less with an average percentage of 1.6% in KPP Pratama Bandung Tegallega, (3) PP 23 of 2018 contributes significantly compared to PP 46 of 2013 towards the Realization of Tax on KPP Pratama Bandung Tegallega.